Seroprevalence and risk factors assessment of Brucella spp. in dairy buffaloes in mainland Greece. - Papapostolou, A; Petridou, EJ; Papageorgiou, K; Stournara, A; Benos, A; Lafi, S; Giadinis, N (Journal of the Hellenic Veterinary Medical Society, 2022)
Brucellosis is an infectious bacterial disease caused by members of genus Brucella, affecting both animals and humans, and resulting in both serious economic losses in animal production sector and deterioration of public health. A cross-sectional study was conducted from January to August of 2018 to determine the seroprevalence and associated risk factors of bovine brucellosis, in Central Macedonia and East Macedonia and Thrace, in mainland Greece. A total of 1,255 blood samples were collected using a simple random sampling technique from dairy buffaloes older than12 months. All serum samples were analyzed with Rose Bengal Test for screening and Complement Fixation Test for confirmation of the positive samples. Accordingly, the overall individual-level seroprevalence of dairy buffaloes in the study area was 0.72% (9/1,255, 95% CI:0.32-1.36%) while the overall herd-level seroprevalence was 15.38% (4/26, 95% CI:6.15-33.53%). Moreover, information was gathered on demographic characteristics of the owners, individual animals and herd level risk factors and other farm characteristics using a questionnaire. Higher prevalence of Brucella spp. was observed in buffaloes bred under intensive and semi-intensive feeding systems, compared to those bred under extensive ones. High seroprevalence of brucellosis was also observed in medium size herds. Two of the herds had recorded history of the disease, the last five years while, in these two herds delays in the implementation of brucellosis eradication programs were revealed. The present study indicated that the occurrence of brucellosis in Greece dairy buffalo farms is at a low magnitude. Even though the seroprevalence is low, it can still be potential hazard for both susceptible animals and humans